1991
DOI: 10.1111/j.1600-0447.1991.tb05544.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐5‐hydroxytryptophan stimulated cortisol escape from dexamethasone suppression in melancholic patients

Abstract: The dexamethasone suppression test (DST) was carried out in 62 depressed patients. At 0800 the postdexamethasone cortisol values were determined and 125 mg L-5-hydroxytryptophan (L-5-HTP) was administered. The second cortisol sample at 0930 revealed a significant enhancing effect for L-5-HTP on the postdexamethasone cortisol values in melancholic patients, whereas no effects were detected in minor depressives. Our results show that L-5-HTP converts some DST suppressors into nonsuppressors, whereas the escape f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The findings of this study extend those of previous reports that showed that L-5-HTP may augment the escape of ACTH and cortisol from suppression by dexamethasone in depression (Maes et al 1991a and that L-5-HTP has a greater effect on HPA-axis hormone secretion in major depression than in normal controls or minor depressed subjects (Meltzer et al 1984;Maes et al 1987). Moreover, a highly significant relationship between the L-5-HTP-induced post-DST !3-endorphin and ACTH responses was found in depression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings of this study extend those of previous reports that showed that L-5-HTP may augment the escape of ACTH and cortisol from suppression by dexamethasone in depression (Maes et al 1991a and that L-5-HTP has a greater effect on HPA-axis hormone secretion in major depression than in normal controls or minor depressed subjects (Meltzer et al 1984;Maes et al 1987). Moreover, a highly significant relationship between the L-5-HTP-induced post-DST !3-endorphin and ACTH responses was found in depression.…”
Section: Discussionsupporting
confidence: 86%
“…To examine the physiopharmacological interactions between the disorders in negative feedback on the HPA axis and serotonergic activity in depression, we studied the effects of L-5-hydroxytryptophan (L-5-HTP), the precursor of serotonin (5-HT), on post-DST ACTH and cortisol values in that illness (Maes et al 1991a. It 0893-133X/96/$15.00 SSDI 0893-133X(95)00238-3 was found that (1) acute administration of L-5-HTP (125 mg or 200 mg PO) significantly increased the escape of ACTH and, consequently, cortisol from suppression by dexamethasone; and (2) that this stimulatory effect of L-5-HTP was significantly greater in major than in minor (i.e., dysthymia, adjustment disorder with depressed mood) depression (Maes et al 1991a. There is now some evidence that L-5-HTP-induced ACTH and cortisol responses in man and the rodent are mediated, at least in part, by 5-HT2A/2C and 5-HTlA receptors (Nakagami et al 1986;Rivier and Plotsky 1986;Van de Kar et al 1989;Fuller 1992;Calogero et al 1993;Chaouloff 1993;Meltzer and Maes 1994).…”
mentioning
confidence: 99%
“…Maes et al (1991a) demonstrated that in DSM-III "major depressives" but not "minor depressives" 5-HTP either augmented existing dexamethasone non-suppression or caused escape from suppression in previous non-suppressors. In a further study, this was confirmed , with the further finding that 5-HTP stimulated escape from suppression not only of cortisol but also of ACTH.…”
Section: Serotonin Precursorsmentioning
confidence: 97%
“…There is evidence that the increase in plasma cortisol and PRL following L-5-HTP in rodents and man are modulated by at least three different postsynaptic receptors, the 5-HT 1A , 5-HT 2A , 5-HT 2C , and 5-HT 3 receptors (for reviews see: Meltzer et al 1982;Fuller and Snoddy 1990;Lesch et al 1990;Fuller 1992;Jorgensen et al 1992;Levy and Van der Kar 1992;Meltzer and Maes 1994). Significantly increased 5-HT precursor (L-TRP or L-5-HTP)induced cortisol responses have been reported to occur in major depression (Meltzer et al 1984;Maes et al 1987Maes et al , 1989aMaes et al , 1989bMaes et al , 1991. It is suggested that the greater L-5-HTP-induced cortisol responses may be attributed to an upregulation of hyperresponsiveness of postsynaptic 5-HT 2A receptors .…”
mentioning
confidence: 99%